(untitled) (Harmoni, 2020)
Attacks against the Ahmadiyah Congregation in Gegerung-Lombok occurred several times in 2005-2006, then continued in 2010. The contestation for the election of the Village Head of Gegerung coincided with the conflict and violence against the Ahmadiyah Community. It was later discovered that the religious leaders in the village were affiliated with one of the candidate village head contestants and were actively involved in the campaign. This study used a qualitative method with data digging techniques carried out through observations and interviews which were carried out in conflict locations and places of refuge in the Ahmadiyah congregation. Meanwhile, interviews were conducted with a number of parties, namely the relevant village head, the Ahmadiyah community, representatives of the NTB government, and the people of Gegerung. The analysis was carried out through data reduction and selecting data relevant to the object of research. The results of this study indicate that the conflict and violence against the Ahmadiyya JamaΓÇÖat is not only caused by differences in beliefs, the existence of a ΓÇ£deviantΓÇ¥ fatwa from the MUI and discriminatory regulations from the West Lombok Regent. Behind the complexity of religious issues, there are other triggers, namely contestation of village head elections and the involvement of political actors in the mass mobilization process. Village Politics, which are in the lowest unit of the bureaucratic system, can actually have an impact on the community and village elites who have financial capital more freely to dominate public discourse. The conflict and violence against Ahmadiyah in Gegerung Village were actually triggered by the intervention of village politicians and religious leaders who made differences in religious understanding as a political commodity.┬á┬á